Editorial 7 (SI1): Kindness in higher education: Fostering the human(e) element of teaching and learning (Journal of Applied Learning and Teaching, 2024)
This editorial introduces the Journal of Applied Learning & Teaching (JALT) 2024 Special Issue on Kindness in Higher Education. Following the tremendous success of the Kaplan Symposium of Learning and Teaching (SoLT) 2023, our issue continues exploring the essential aspects of Garrison’s (2016) Community of Inquiry (CoI) model, with a specific emphasis on the three forms of ‘presence’: social, cognitive, and teaching. This special collection features six research articles and one interview, each looking into the multifaceted role of kindness within scholarly contexts in higher education. The opening systematic literature review identifies key themes and proposes a research agenda for future studies. Subsequent articles examine students’ and teachers’ perceptions of social and cognitive presence, effective language teaching components, and innovative pedagogical practices. The final research article showcases a caring hybrid-flexible (HyFlex) pedagogy in initial teacher education. An insightful interview with Professor James Adonopoulos of Kaplan Business School (KBS) underlines the institutional commitment to student-centred approaches and integration of kindness into educational practices. Collectively, these contributions emphasise the significance of kindness in fostering inclusive, supportive, and effective learning environments, offering diverse insights and pragmatic solutions for educators, policymakers, and institutions.